Barriers and experiences of patients with type 2 diabetes mellitus in maintaining dietary patterns and glycemic control at Bhayangkara TK II Hospital, Medan - Laura Elisa Tampubolon; Cristina Br. Sinulingga; Masryna Siagian; Widya Yanti Sihotang; Andry Simanullang; Nila Sari (Fakultas Kedokteran, Kedokteran Gigi, dan Ilmu Kesehatan, 2026)
Background: Type 2 diabetes mellitus (T2DM) is a chronic metabolic disorder requiring continuous self-management, including dietary regulation and glycemic control. However, many patients face barriers in maintaining these behaviors. This study aimed to explore the barriers and experiences of T2DM patients in maintaining dietary patterns and glycemic control at Bhayangkara TK II Hospital, Medan. Method: A qualitative phenomenological study was conducted. Participants were selected using purposive sampling, including 5 T2DM patients (aged >45 years, diagnosed >5 years), 5 family caregivers, and 1 internist. Data were collected through in-depth interviews and analyzed using Colaizzi's seven-step method. Results: Five themes emerged from patient interviews: (1) emotional response to diagnosis and lifestyle adaptation; (2) health monitoring (blood glucose checks and medication adherence, including complementary therapy use); (3) lifestyle and dietary management (difficulty resisting cravings and diet discipline); (4) family support (instrumental and emotional); (5) future hopes (productivity and quality of life). From family caregivers, five themes emerged: role in diet management, instrumental support for healthcare access, psychological and financial burden, social and cultural navigation strategies, and family hopes. From the physician, four themes emerged: dynamics of patient adherence and barriers, perspectives on patient experience and quality of life, clinical management and interventions, and development of sustainable strategies and solutions. Conclusion: T2DM self-management is a dynamic and complex process involving emotional adaptation, dietary challenges, family support, and healthcare engagement. Strengthening patient self-efficacy, family involvement, and practical strategies such as bringing home-cooked meals are essential for improving glycemic control and quality of life.